Decision support system application in disaster management - Yilin, Li; Zhaoji, Fu; Kowthalam, Vijay Rathnam; Guangfa, Wu; Abdul Rahim, Yusrina; Maidin, Siti Sarah; Yahya, Norzariyah (CITEDNESS, 2024)
Disasters such as earthquake, flood, fire, and tsunami result in catastrophic human suffering, loss of property and other negative consequences. The continues threats of future disasters enforce human to find best possible ways to detect and take premeasured actions based on calculated risks to reduce these negative impacts of disasters. With the rapid technologies advancement, it will not be able to eradicate disasters in totality, however with the application of decision support system (DSS), it will bring many beneficials to the Disaster Management especially when the disaster response team must make quick decision during the stressful time and/or within the complex situation with more reliable information. This study conducted to understand the roles of DSS in Disaster Management and its impact.